Deteksi Dini Kanker Leher Rahim (Kanker Serviks) Dengan Metode IVA - Yuliani, Istri; Lusia, Budi Astuti; Widiati, Endang Nur (Universitas Respati Yogyakarta, 2020)
Background: Cervical cancer is number four disease in the world that causes the most death. It is found more often in developing countiies than in the developed ones. In Indonesia it is the second disease after breast cancer. It is 23.4 per 100,000 people. The death rate is 13.9 per 100,000 people. It shows that each year 50 women die because of cervical cancer. If this disease is detected earlier, it can be cured. That is why mature women, especially those actively having sexual intercourse should detect earlier from cervical cancer at least once in a year. It is important to maintain health as well as to detect cervical cancer earlierMethod: Cervical cancer early detection with IVA method, held in 9 October 2019 in Puri Adisty Clinic with 40 participants.Result: Most of the participants were more than 40 years old. Most of them had 2 children. Most of them had senior high school education. They marriedat the age of 20 to 35 years old. The IVA examination showed that all of the participants were in negative category, 15% of them had erotion of the portionis uterine and 85% of them had healthy cervics.Conclusion: No participant in IVA test had suspicious symptoms towards cervical cancer. In other words IVA test was in negative category.Key words: detection, cancer, cervics, IVA